2011
DOI: 10.1007/s00268-011-1139-y
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Controlled, Randomized Study of Intraoperative Colonic Lavage Versus Stent Placement in Obstructive Left‐sided Colonic Cancer

Abstract: In our setting, the use of a stent and scheduled surgery is safer than IOCL and is associated with lower morbidity, shorter hospital stay, and equally good long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
165
5
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(184 citation statements)
references
References 55 publications
5
165
5
9
Order By: Relevance
“…15 This guideline is based on the evidence from eight systematic reviews with meta-analysis comparing preoperative stenting with emergency resection for left-sided colonic malignant obstruction, 11,[36][37][38][39][40][41][42] with assimilated data from up to seven RCTs. [43][44][45][46][47][48][49] Three of those RCTs were closed early due to adverse outcomes in the SEMS group (higher 30-day morbidity related to stent perforation), 43,44 or high anastomotic leak rate in the emergency surgery group. 48 The most recently published meta-analysis found that SEMS as a bridge to surgery (n = 195) compared to emergency surgery (n = 187) had a lower overall morbidity (33.1% vs 53.9%, P = 0.03), a higher successful primary anastomosis rate (67.2% vs 55.1%, P < 0.01), and a lower permanent stoma rate (9% vs 27.4%, P < 0.01); however, there was no statistical difference in post-operative mortality (10.7% vs 12.4%).…”
Section: Sems As a Bridge To Elective Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…15 This guideline is based on the evidence from eight systematic reviews with meta-analysis comparing preoperative stenting with emergency resection for left-sided colonic malignant obstruction, 11,[36][37][38][39][40][41][42] with assimilated data from up to seven RCTs. [43][44][45][46][47][48][49] Three of those RCTs were closed early due to adverse outcomes in the SEMS group (higher 30-day morbidity related to stent perforation), 43,44 or high anastomotic leak rate in the emergency surgery group. 48 The most recently published meta-analysis found that SEMS as a bridge to surgery (n = 195) compared to emergency surgery (n = 187) had a lower overall morbidity (33.1% vs 53.9%, P = 0.03), a higher successful primary anastomosis rate (67.2% vs 55.1%, P < 0.01), and a lower permanent stoma rate (9% vs 27.4%, P < 0.01); however, there was no statistical difference in post-operative mortality (10.7% vs 12.4%).…”
Section: Sems As a Bridge To Elective Surgerymentioning
confidence: 99%
“…[43][44][45][46][47][48][49] Three of those RCTs were closed early due to adverse outcomes in the SEMS group (higher 30-day morbidity related to stent perforation), 43,44 or high anastomotic leak rate in the emergency surgery group. 48 The most recently published meta-analysis found that SEMS as a bridge to surgery (n = 195) compared to emergency surgery (n = 187) had a lower overall morbidity (33.1% vs 53.9%, P = 0.03), a higher successful primary anastomosis rate (67.2% vs 55.1%, P < 0.01), and a lower permanent stoma rate (9% vs 27.4%, P < 0.01); however, there was no statistical difference in post-operative mortality (10.7% vs 12.4%). This data suggests some advantages of SEMS use over emergency surgery, although with no difference in short-term mortality, the benefit of SEMS placement in this setting is less clear.…”
Section: Sems As a Bridge To Elective Surgerymentioning
confidence: 99%
“…Nous disposons de beaucoup de données sur les résul-tats des prothèses. Il s'agit en particulier de larges séries rétrospectives qui ont inclus au total 3 581 patients [13][14][15], de six études randomisées [16][17][18][19][20][21] et de sept méta-analyses [22][23][24][25][26][27][28]. À noter que ces méta-analyses s'appuient en partie sur des travaux rétrospectifs avec des objectifs pas toujours clairement définis.…”
Section: Succès Et Complications Des Endoprothèses à Court Termeunclassified
“…A few randomized controlled trials and a cohort study have shown a significantly higher local disease recurrence rate with SEMS use than emergent surgery [7][8][9][10] . According to the European Society of Gastrointestinal Endoscopy (ESGE) guidelines, SEMS placement as a BTS is not recommended as a standard treatment for potentially curable patients with obstructive colorectal cancer [11] .…”
Section: Introductionmentioning
confidence: 99%